Analysis of Flavonids and Terpenoids in Ethanol Extract of Colocasia esculenta L. (Schoot) Stalk and Leaves - Erni Rustiani; Aulia Fitriani; Sri Wardatun (Journal of Tropical Pharmacy and Chemistry, 2021)
Colocasia esculenta L. (Schoot) is a widely used plant in developing countries in Asia, Africa, and Central America. The parts of the Colocasia plant that can be used are the tubers, stalks, and leaves. There has not been much research on the content of this plant. The study aims to determine the flavonoids and terpenoids in the ethanol extract of Colocasia stalk and leaves. The maceration method with 70% ethanol solvent and drying with vacuum evaporator. Determination of flavonoid levels based on quercetin marker compounds using AlCl3 reagent by UV-Vis spectrophotometry. The terpenoid levels were carried out gravimetrically with petroleum ether as a solvent. The results showed that the ethanol extract of Colocasia stalk and leaf contained flavonoids, respectively 3.18 +0.0581% and 4.33 +0.0285%, while the results of the terpenoid levels for stalks were 7.10 +0.0676% and leaves were 8.39 +0.0023%.